The Interplay between Topic Shift and Focus in the Dynamic Construction of Discourse Representations - Yang, Xiaohong; Zhang, Xiuping; Wang, Cheng; Chang, Ruohan; Li, Weijun (Frontiers in Psychology, 2017)
Previous studies have suggested that focusing an element can enhance the activation of the focused element and bring about a number of processing benefits. However, whether and how this local prominence of information interacts with global discourse organization remains unclear. In the present study, we addressed this issue in two experiments. Readers were presented with four-sentence discourses. The first sentence of each discourse contained a critical word that was either focused or unfocused in relation to a wh-question preceding the discourse. The second sentence either maintained or shifted the topic of the first sentence. Participants were told to read for comprehension and for a probe recognition task in which the memory of the critical words was tested. In Experiment 1, when the probe words were tested immediately after the point of topic shift, we found shorter response times for the focused critical words than the unfocused ones regardless of topic manipulation. However, in Experiment 2, when the probes words were tested two sentences away from the point of topic shift, we found the facilitation effect of focus only in the topic-maintained discourses, but not in the topic-shifted discourses. This suggests that the facilitation effect of focus was not immediately suppressed at the point of topic shifting, but when additional information was added to the new topic. Our findings provide evidence for the dynamic interplay between global topic structure and local salience of information and have important implications on how activation of information fluctuates in mental representation.